426 Percutaneous or surgical access for transfemoral transcatheter aortic valve implantation: a propensity matched analysis of a multicentre registry. (8th December 2021) - Bruno, Francesco; Crimi, Gabriele; Ascenzo, Fabrizio D'; Marzo, Vincenzo De; Scudeler, Luca; Marco, Federico De; Oreglia, Jacopo; Testa, Luca; Gorla, Riccardo; Esposito, Giuseppe; Spaccarotella, Carmen; Soriano, Francesco; et al.
Abstract: Aims: The transfemoral (TF) approach appeared to be the safest and the broadest used approach in TAVI, characterized by a lower rate of periprocedural bleedings and vascular complications and is currently recommended by the guidelines as a first line approach when feasible. If in the early experience TF access was achieved using a surgical cutdown approach, through the last years, there has been increasing evidence of the safety and efficacy of a fully percutaneous approach over a surgical access, albeit available evidences are controverting and mostly including first generation prostheses and high risk patients. The aim of the study is to compare percutaneous and surgical access in a large, real-word, multicentre of TF TAVI. Methods and results: Consecutive patients undergoing successful TF TAVI were prospectively enrolled in local clinical registries of five high volume centres in Italy: IRCCS Ospedale Policlinico San Martino (Genoa), IRCCS Policlinico San Donato (Milan), Città Della Salute e della Scienza, (Turin), Ospedale Niguarda Ca' Granda (Milan), Magna Graecia University, (Catanzaro), between January 2014 to December 2019. Univariate and multivariate analysis using IPTW were performed. A total of 1946 TF TAVI patients (female 42.8%) were prospectively included. Patients underwent surgical access had a significantly higher surgical risk (STS score of 8.9 vs. 6.4, P  < 0.001, and EuroSCORE of 15.1 vs. 8.7, P  < 0.001, respectively). Overall survival was comparable between the two groups (HR: 1.14, 95% CI: 0.76–1.71). Patients who underwent surgical access experienced more VARC-2 major and VARC-2 minor vascular complications (13% vs. 7%, P  = 0.003 and 11% vs. 6.1%, P  = 0.007, respectively) and more VARC-2 major/life threatening and minor bleeding (27.4% vs. 17.8, P  = 0.001, and 9.6% vs. 2.1%, P  < 0.001, respectively). After IPTW adjustment, surgical access was associated with an increased risk of major vascular complications (HR: 3.32, 95% CI: 1.84–5.97), minor bleeding (HR: 4.24, 95% CI: 1.16–15.54) and stage 2–3 AKI (HR: 2.60, 95% CI: 1.07–6.33). Conclusions: The performance of the percutaneous transfemoral TAVI approach was safe and feasible and resulted in fewer major vascular complications, bleedings and AKI than the surgical femoral isolation. Procedural time and hospital length were also lower in the percutaneous group. Routine application of the percutaneous approach might reduce acute complications in patients undergoing transfemoral TAVI and reduce procedural time and hospital length.